Implementation of the learning civic community model in financial accounting learning process continuation: Economic education college student - Warneri Warneri; Jagad Aditya Dewantara (Universitas Negeri Yogyakarta, 2021)
This study aims to determine whether the Civic Community Learning model that uses the Citizenship Economics approach, which can improve the acquisition of learning outcomes and student learning activities in the Advanced Financial Accounting course, is right on the topic of accounting for branch companies in Economic Education Studies Program. The approach used in this research is qualitative. The method used is action research. Researchers are the key instrument. Data collection techniques are carried out through learning outcomes tests and rubrics for assessing student activities, data analysis is inductive, and qualitative research results emphasize meaning rather than generalization first. Establish performance indicators for the success of each given action. The data sources in this study were students in the third semester of the 2020/2021 academic year majoring in social studies education, economic education study program. This study involved 33-semester 3rd students of the economics study program for the 2020/2021 academic year. This study shows that the acquisition of student learning outcomes and student learning activities taught with the Learning Community learning model in the subject matter of Advanced Financial Accounting, Corporate Accounting Branch has increased.